Exploring the Disparity in Indoor/Outdoor Time and Radon Exposure as Possible Factors Contributing to the Unexpected Increase in Lung Cancer Risk among Non-Smoking Women - Safari, Arash; Mortazavi, Seyed Alireza; Ghadimi-Moghadam, Abdolkarim; Haghani, Masoud; Mortazavi, Seyed Mohammad Javad; Sihver, Lembit (Journal of biomedical physics & engineering, 2024)
According to a NIH study, Lung cancer among individuals who have never smoked is more prevalent in women and occurs at an earlier age than in smokers. The rise in lung cancer rates among female non-smokers might be linked to radon inhalation and should be further investigated. Our theory is based on the differences in radon exposure between males and females, which can be attributed to the variations in time spent indoors versus outdoors. Over the past few years, the smoking rates have shown a steady decline in the United States and other developed countries. This decrease in smoking prevalence has led to a new shift in the primary risk factors associated with lung cancer. Although tobacco smoke historically served as the primary cause of lung cancer, the reduction in smoking rates has allowed other risk factors, such as radon exposure, to come to the forefront. Given that women in certain countries, on average, might spend more time indoors compared to men, they are potentially exposed to higher levels of radon. This increased exposure could explain the rising rates of lung cancer among female non-smokers. The theory is still in its nascent stages and requires further research and validation. However, if proven correct, it could significantly alter our understanding of lung cancer risk factors and lead to new prevention. It is therefore crucial to expedite the review and publication of this theory, given its potential implications for public health.